Calcified amorphous tumour of the heart: presentation of a rare case operated using minimal access cardiac surgery. (3rd June 2011) - Greaney, Lisa; Chaubey, Sanjay; Pomplun, Sabine; St. Joseph, Emma; Monaghan, Mark; Wendler, Olaf
Abstract : Calcified amorphous tumour (CAT) of the heart is a rarely reported non-neoplastic cardiac mass. The authors report a 69-year-old female with long-standing severe asthma and on home oxygen, who presented with a 2 cm mobile mass in the left ventricular outflow tract and symptoms of left heart failure and stroke. During minimal access cardiac surgery, a CAT was found attached to the base of the mitral valve. The tumour was removed and the patient had an uneventful postoperative course. The authors present their experience with this patient and review the current literature on this rare kind of tumour.